Anaphylaxis and intimate behaviour. Issue 5 (October 2017) - Liccardi, Gennaro; Caminati, Marco; Senna, Gianenrico; Calzetta, Luigino; Rogliani, Paola
Abstract : Purpose of review: Intimate behaviours may represent an unusual way of exposure to a culprit allergen, or the frame for sex-related allergies due to triggers typically linked to that situation. The present review aims at summarizing the state of the art about the topic, in order to spread the awareness and the basic know-how in the field of sexual-related allergies. Recent findings: Kiss-related IgE-mediated reactions are caused in sensitized partners mainly by the passive transport of allergenic molecules through saliva, skin or oral mucosa. It has also been recently suggested that kissing may act as an epicutaneous way for induction of allergic sensitization. Among food and drugs, not only but mostly, peanuts and beta-lactams, respectively, are the usual trigger. Although controversial, 1-hour wait before kissing and a proper mouth cleaning have been suggested as prevention strategies. Sexual intercourse related local or systemic symptoms can be caused by seminal plasma hypersensitivity, an IgE-mediated/type IV reaction due to prostate-specific antigen, which carries high homology to the canine prostatic kallikrein (Can f 5). Although applied to few patients, successful desensitization and immunotherapy protocols have been proposed. Summary: Intimate behaviours are possible modalities of contact with the allergen. The exact prevalence of such hypersensitivity reactions is not known, but for its implications on Quality of Life and reproductive wishes, the possible link between sex and allergy should become part of the personal culture of clinical allergists and every clinician, in order to extend and improve the diagnosis of unusual or unexplained conditions.